Estudio del comportamiento del fuego mediante simulación de incendios forestales en Chile - Castillo Soto, Miguel; Garfias Salinas, Roberto (Geographicalia, 2014)
We performed a statistical validation of forest fire simulator KITRAL System developed by the Forest Fire Laboratory at the Universityof Chile, by collecting information from real fires occurred in rural areas of the Eighth Region of the country. We defined 16 variables related to the size and geometry of the burned areas, which were studied by multivariate analysis. The paper discusses and analyzes the similarity of the predictions with the data observed in real fires. The most important differences are found in fires smaller than 0.5 ha, which corresponded to an expected result, due to poor reliability of the information in very smallareas, where data such as topography, are generated by interpolation techniques. However, for fires larger than 5 ha, the levels of similarity ranged between 85 and 94%. As for the comparison of specific results of fire behavior, in 15 of the 16 variables analyzed (93% of cases), no significant differences were found between simulated and actual values,confirming the validity in the estimates.
Keywords: KITRAL; simulation; fire behavior; wildfire.